Mechanical properties of PE/E-glass commingled yarn wound pipes and pipe elbows - Bekem, Aylin; Unal, Ahmet (CARL HANSER VERLAG, 2018)
PE pipes and fittings are used in water, chemicals, as well as gas supply and distribution. In most applications, pressurized piping systems are needed. When pressure grade is increased, pipe wall thickness increases to carry the load, and the system becomes heavier and less flexible. Reinforcing the polymer could be an alternative without the need to thicken a pipe wall. It is hard to reinforce PE however, because PE does not easily adhere to fiber. In this study, the filament winding process was applied to PE pipes and elbows. PE/E-glass commingled yarn was used to make it easier to reinforce the PE. The filament winding process was modified for the commingled yarn whereby temperature and pressure were increased. Helical and circumferential winding was carried out. The thin PE film was coated. Mechanical tests and computer structural analysis were done and results were compared.
Keywords: PE/E-glass commingled yarn; winding; pipe; pipe elbow; mechanical properties; Materials Science